PtrA Is Functionally Intertwined with GacS in Regulating the Biocontrol Activity of Pseudomonas chlororaphis PA23 - Shah, Nidhi; Klaponski, Natasha; Selin, Carrie; Rudney, Rachel; Fernando, W. G. Dilantha; Belmonte, Mark F.; de Kievit, Teresa R. (Frontiers in Microbiology, 2016)
In vitro inhibition of the fungal pathogen Sclerotinia sclerotiorum by Pseudomonas chlororaphis PA23 is reliant upon a LysR-type transcriptional regulator (LTTR) called PtrA. In the current study, we show that Sclerotinia stem rot and leaf infection are significantly increased in canola plants inoculated with the ptrA-mutant compared to the wild type, establishing PtrA as an essential regulator of PA23 biocontrol. LTTRs typically regulate targets that are upstream of and divergently transcribed from the LTTR locus. We identified a short chain dehydrogenase (scd) gene immediately upstream of ptrA. Characterization of a scd mutant revealed that it is phenotypically identical to the wild type. Moreover, scd transcript abundance was unchanged in the ptrA mutant. These findings indicate that PtrA regulation does not involve scd, rather this LTTR controls genes located elsewhere on the chromosome. Employing a combination of complementation and transcriptional analysis we investigated whether connections exist between PtrA and other regulators of biocontrol. Besides ptrA, gacS was the only gene able to partially rescue the wild-type phenotype, establishing a connection between PtrA and the sensor kinase GacS. Transcriptomic analysis revealed decreased expression of biosynthetic (phzA, prnA) and regulatory genes (phzI, phzR, rpoS, gacA, rsmX, rsmZ, retS) in the ptrA mutant; conversely, rsmE, and rsmY were markedly upregulated. The transcript abundance of ptrA was nine-fold higher in the mutant background indicating that this LTTR negatively autoregulates itself. In summary, PtrA is an essential regulator of genes required for PA23 biocontrol that is functionally intertwined with GacS.